EFFECT OF LIGHTING COLOR ON HUMAN PERFORMANCE - Ratri Atmoko Benedictus (MANASA, 2017)
Workplace with poor in lighting directly influences the emergence of eyestrain among workers. In long term exposure, it may be resulted in occupational stress, increase the psychological burden and even lead to depression among workers. This study tested whether the particular color of lighting influence work performance. 25 participants were involved in this experimental study that had been performed at Human Factor Engineering Laboratory of Hochschule Niederrhein. Three color combinations of light were provided as independent variable, namely white-white, white-pink, and white-blue. Schätzskalen zum kurzfristigen Beanspruchungserleben (Scale for short-term stress estimation) from Hacker et al. was utilized to measure several aspects of work performance as dependent variable, particularly performance efficiency, achievement motivation, and concentration during work. Analysis of variance resulted that there is no difference in the performance between the lighting color groups on the second stage of the experiment. One Factorial Analysis further resulted in the difference on work performance within subjects which indicates the increasing performance of each experimental stage. And last, by Two Factorial Analysis,  the result indicated that there are differences between the gender groups at each stage of the experiment in terms of concentration and working motivation. The mean difference between gender groups shows that female’s groups have higher concentration levels. Whereas, the male’s group is higher in terms of work motivation. Considering the contribution of lighting for human performance, It is necessary to consider the quality of light in the workplace, not only in terms of illumination level but also the color of light.